Wages and incentive instruments for enhancing the performance of construction industry employees - Tichá, Alena (Array, 2020)
The aim of the article is to present quantitative development of wages and incentive instruments in the Czech Republic during the recent period and at the same time to provide an insight into the emerging changes in the labor market brought by the industry and the construction industry digitization. Strong demand for increased corporate social responsibility of the companies in the technical, economic and environmental protection and care sectors, and in particular in mutual communication between market partners, has had and will have an impact on wage policy and creation of employer wage systems. This article briefly gives the insight into what visions and strategies this situation brings into the construction industry field.